Detection of circulating epithelial cells in the blood of patients with breast cancer: comparison of three techniques - Ring, A E; Zabaglo, L; Ormerod, M G; Smith, I E; Dowsett, M (British journal of cancer, 2005)
This study compares the sensitivities and specificities of three techniques for the detection of circulating epithelial cells in the blood of patients with breast cancer. The number of circulating epithelial cells present in the blood of 40 patients with metastatic breast cancer and 20 healthy volunteers was determined by: immunomagnetic separation (IMS) and laser scanning cytometry (LSC), cell filtration and LSC and a multimarker real-time RT–PCR assay. Numbers of cytokeratin-positive cells identified and expression of three PCR markers were significantly higher in the blood of patients with breast cancer than in healthy volunteers. Using the upper 95% confidence interval of cells detected in controls to determine positive patient samples: 30% of patients with metastatic breast cancer were positive following cell filtration, 48% following IMS, and 60, 45 and 35% using real-time RT–PCR for cytokeratin 19, mammaglobin and prolactin-inducible peptide. Samples were significantly more likely to be positive for at least one PCR marker than by cell filtration (83 vs 30%, P <0.001) or IMS (83 vs 48%, P <0.001). The use of a multimarker real-time RT–PCR assay was therefore found to be the most sensitive technique for the detection of circulating epithelial cells in the blood of patients with breast cancer.